Teacher Talk Time as a Means to Develop Learners Communicative Skills in an EFL Class - IFALAMBANGA MUBIKABALA, Damien (International Journal of Scientific Research and Management (IJSRM), 2022)
The English curriculum in the Democratic Republic of Congo forecasts for the teaching of English from the first year of secondary school. Most students who finish high school are unable to speak English correctly, even to engage in a ten-minute conversation with friends. My experience as an English teacher for several years in high school shows that there are many factors that hinder the learner to assimilate the English language: the lack of motivation on the part of pupils, lack of appropriate textbooks, inadequacy of the national curriculum, laziness and fear on the part of pupils, monopolization of speech by the teacher model and use of French to teach English. This teacher model leads to the teacher’s share of monopolizing speech during classroom instruction. In this study, I want to show that the Teacher Talk Time during the transmission of his lesson should decrease because this affects the learner time to develop communicative skills. The suggested model for teaching English as a second language provides 25% of the time for the teacher and 75% for the learner so that the teacher is the facilitator, coach, guide, moderator, a helper. English must be taught as a language but not as a subject.The difficulties that learners have to express themselves fluently in English come greatly due the teacher who does not give a lot of time to learners to practice the English language because he talks too much. Therefore, this work shows that ‘Teacher Talking too Much’ in the class does not give  opportunities to the learner to develop oral skill and  master English as a Foreign Language for our secondary schools in Bandundu town in particular and those of the Democratic Republic of Congo in general.